Citrus Diseases Exotic to Florida: Citrus Tristeza Virus– Stem Pitting (CTV-SP) - Kuang Ren Chung; Ronald H. Brlansky (EDIS)
Citrus is susceptible to a large number of diseases caused by plant pathogens. Economic losses due to plant diseases can be severe, but fortunately, not all pathogens attacking citrus are present in Florida. Major citrus diseases currently present in Florida include: Alternaria brown spot, blight, citrus canker, greasy spot, melanose, Phytophthora-induced diseases (foot and root rot, brown rot), postbloom fruit drop (PFD), scab, and tristeza. An exotic, destructive disease called citrus greening (Huanglongbing) has recently been found in Florida. Any exotic diseases, if introduced, will increase production costs and decrease profitability for Florida growers. Exotic diseases affect the viability of the industry or the varieties that could be profitably grown. Background information for each exotic citrus disease will be presented in a series of fact sheets to: 1) provide a basis for evaluating exotic pathogens that may pose potential risks to Florida citrus; and 2) create a decision-making framework to prevent their introduction and spread. This paper will discuss Citrus tristeza virus-Stem Pitting (CTV-SP) disease.